Extreme variability in an active galactic nucleus: Gaia16aax. Issue 1 (23rd January 2020) - Cannizzaro, G; Fraser, M; Jonker, P G; Pringle, J E; Mattila, S; Hewett, P C; Wevers, T; Kankare, E; Kostrzewa-Rutkowska, Z; Wyrzykowski, Ł; Onori, F; Harmanen, J; et al.
ABSTRACT: We present the results of a multiwavelength follow-up campaign for the luminous nuclear transient Gaia16aax, which was first identified in 2016 January. The transient is spatially consistent with the nucleus of an active galaxy at z = 0.25, hosting a black hole of mass 6× 10^8 M_ . The nucleus brightened by more than 1 mag in the Gaia G band over a time-scale of less than 1 yr, before fading back to its pre-outburst state over the following 3 yr. The optical spectra of the source show broad Balmer lines similar to the ones present in a pre-outburst spectrum. During the outburst, the H α and H β emission lines develop a secondary peak. We also report on the discovery of two transients with similar light-curve evolution and spectra: Gaia16aka and Gaia16ajq. We consider possible scenarios to explain the observed outbursts. We exclude that the transient event could be caused by a microlensing event, variable dust absorption or a tidal encounter between a neutron star and a stellar mass black hole in the accretion disc. We consider variability in the accretion flow in the inner part of the disc, or a tidal disruption event of a star 1 M_ by a rapidly spinning supermassive black hole as the most plausible scenarios. We note that the similarity between the light curves of the three Gaia transients may be a function of the Gaia alerts selection criteria.